Science and practice of strength training - Zatsiorsky, Vladimir M., 1932-; Kraemer, William J., ....- (Champaign, IL : Human Kinetics, 2006)
This book is for those readers interested in muscular strength and ways to enhance its development. It is developed from the vast experience of both authors, who bring to the text documented experiences of more than 1,000 elite athletes, including from Olympic, world, continental and US national record holders. Written for the practitioner, it provides a straightforward examination of the fundamental concepts and principles readers need to understand in order to make decisions on what might be appropriate in the programme design for their athletes. The integration of coaching theory and scientific underpinnings in this new edition continues to promote a more sophisticated approach to strength training. Recensie(s) It's now in its second edition and it's a great book. Here's why. The authors have combined Eastern European and North American resistance training practices to present a truly global perspective on current theories on how athletes should train. Compared to the first edition, this edition is much more practical. Bigger Faster Stronger
Keywords: Krachttraining